THE USE AS BIO-INDICATORS SPONGE Callispongia sp. HEAVY METALS CD METAL CONTAMINATION IN THE WATERS OF THE AMBON BAY - A. N. Siahaya; Alfian Noor; Nicole de Voogd (Pattimura University, 2017)
The deposition of heavy metals in Ambon Bay was investigated by using sponge species (Callispongia sp.) as bioindicator. Two different sampling schemes are discussed in this paper: a random sampling scheme with 8 sampling sites distributed over the whole territory of Ambon Bay. Unwashed, dried samples were totally the concentrations of metal elements were determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES). Heavy metal Cd. The median concentrations and statistical parameters of elements were discussed by comparing two sampling schemes. The results of both sampling schemes are compared with the results of other the location of the net. Different levels of the contamination valuated by the respective contamination factor (CF) of each element are obtained for both sampling schemes, while the local contamination identified like cadmium metallurgy and cement industry, oil refinery, mining industry, and transport have been the same for both sampling schemes. In addition, the natural sources, from the accumulation of these metals in sponge caused by metal-enriched soil, associated with activity in the land were pointed as another possibility of local factors.